Aramaic - Kutscher, E. Y.
< T. A. Sebeok (Ed.), Current Trends in Linguistics, VI, The Hague/Paris 1971, Mouton, p. 347-412; history of research since 1939; Aramaic and Akkadian: 99-101; Aramaic and Old Persian: 130-142.